Evaluation of taste quality of Keemun congou black tea during ripening and the effect of this quality on antioxidant capacity and in vitro inhibition of α-amylase and α-glucosidase - Wenjing Huang; Zhibin Ye; Yida Wu; Tianzi Yu; Wei Zhao; Zihao Qi; Yanqun Jiang; Qiuyan Liu; Guofu Lu; Jingming Ning (Food Chemistry: X)
Ripening is a key process driving the transformation of non-volatiles in Keemun congou black tea (KCBT), affecting its flavour profile and health functions. In this study, taste was quantitatively evaluated by using sensory and biomimetic electrodes and by employing metabolomic techniques. The results revealed that the content of polyphenols was greatly affected by ripening, catechins and flavonoids reduced by 63.5 % and 9.2 %, respectively, and theaflavins increased by 14.6 %, thereby attenuating the bitterness and astringency of the tea infusion while enhancing its sweetness and mellowness. Experiments regarding the inhibition of α-amylase and α-glucosidase activity and scavenging of 2,2-diphenyl-1-picrylhydrazyl radical revealed that ripening triggered the cascade reaction of polyphenols to form catechin polymers and flavonoid glycosides, thereby changing the dual biological functions of hypoglycaemia and free radical scavenging in vitro. Our study confirms the key role of ripening in enhancing the taste quality and potential health functional activities of KCBT.